Online Reading Culture among Indonesian EFL Students at Tertiary Education Level - Kirana Safa Dewi; Sahiruddin Sahiruddin (Studi Budaya Nusantara, 2020)
During COVID-19 pandemic, online learning has been regulated to be applied in all education levels by the ministry of education and culture in Indonesia. This has brought about the changes in learning culture (Kim, 2020) from face-to-face or traditional classroom to online virtual classroom. One of the impacts of online learning is students are required and encouraged to read online materials as to set up new online reading culture. The swift of reading mode from paper-based to online-based in teaching and learning process has motivated this research as to investigate students’ strategies in reading from online sources for class activities. This study involves finding out metacognitive strategies using the Online Survey of Reading Strategies (OSORS) which already modified by Anderson (2003). Some potential differences of the online reading strategy used by both groups are also scrutinized. The result of the current study reveals that that majority of the students use Problem Solving Strategies. Pedagogical implications of the study are discussed.